Haiti : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
This note reviews the effects of dollarization on the ability of the Bank of the Republic of Haiti (BRH) to conduct monetary policy and the risks to macroeconomic stability and the banking system. Haiti's external indebtedness has been compared with that of countries eligible for debt relief under the Initiative for Highly Indebted Poor Countries (HIPCs). Haiti's accession to the Caribbean Common Market and the impact of trade liberalization measures on the strategic rice sector is discussed. The causes of poverty in Haiti are also analyzed.